Genres of Social Advertising - Tatyana V. Anisimova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2018)
The article continues the author's series of works proving that genre forms in all types of advertising do not have an independent character, they are borrowed from other discourses. There are three forms of using "alien" genres – borrowing, styling and imitation. Actually, borrowing assumes that the original genre naturally and without reconsideration fits into the form of the poster. This role is played by the genres of direct communication (request, advice, demand). Styling is expressed in the reproduction of the form of the genre, typical of another discourse, but not characteristic of social advertising (announcement, poster, toast). At the same time, the advertising content is presented directly and fairly fully. Simulation differs in the use of game forms for the purpose of attracting attention to the problem (news announcement, dictionary article, note). A parallel is made between the types of commercial advertising and the forms of using genres in social advertising. The commodity advertising implies the use of information at the first stage of the life cycle, while in social advertising the genre of slogan is in demand at the stage of primary formation of the attitude to the idea. The direct appeals to the addressee by means of stimulating speech genres is peculiar of adverting advertisements, relevant at the second stage of the product life cycle. A variety of atypical genre forms (stylization) perform the function of reinforcing commodity advertising in social advertising. The parodying of genre forms of other types of discourse corresponds to reminding commodity advertising.